Millets (Shree Anna): A Boon to Health - Dr. Ranu Shukla N.E.T. Ph.D. (Botany),; Rohit Kumar Verma, (International Journal of Scientific Research in Science and Technology, 2025)
Cereal grains like rice and wheat are the major components of Indian diet. Diets based solely on wheat and rice lack many minerals, dietary fibers and antioxidants in adequate amount. Non-communicable diseases like diabetes, cardiovascular diseases and cancer are on the rise in the country. In spite of various efforts, under-nutrition in the form of iron deficiency anaemia among women and children is also increasing. According to World Health Organization, 820 million people in the world suffer from chronic hunger. In 2021 Global Hunger Index, India has been ranked at 101st position out of the 116 countries with a score of 27.5, showing a serious level of hunger present in the country. Therefore, in order to overcome such serious type of condition, the agriculture production system is required to take important decisions to mainstream the production of crops that are marginally cultivated in regions with limited resources. Minor millets or small millets has the potential to rescue the poor and most vulnerable sections of the population and provide food and nutrition security to the nation especially during situations such as the current pandemic of COVID 19.